A new semiparamtetric approach to analysing Conditional Income Distributions - Alexander Sohn; Nadja Klein; Thomas Kneib (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In this paper we explore the possibility of the application of GAMLSS regression techniques for the analysis of income distributions in Germany following the reunification. We find that conditional income distributions can generally be modelled using the three parameter Dagum distribution and our results hint at an even more pronounced effect of skill-biased technological change than can be observed by standard mean regression.
Keywords: C13; D31; J31; 330